TINJAUAN YURIDIS TRANSAKSI JUAL BELI PROPERTI MELALUI PRE-PROJECT SELLING - Denise Elysia; Zain Lestya Pradana; Roniko Putra Julio Affani; Arif Rahman (Jurnal Education and Development, 2020)
Housing is a basic human need, the fulfillment of food and clothing is a measure of community welfare. However, housing prices continue to rise making it difficult for people to have it. Transaction of buying and selling shelter through Pre Project Selling makes it easy for people to have a place to live, but people have fears. How to guarantee the certainty of the residence is built and legal protection for people who buy the residence. The legal research method used is normative juridical, by reviewing through the Statute Approach and Conceptual Approach approaches. The basis for the Pre Project Selling is the principle of freedom of contract. The rights of the Pre Project Selling buyers, will be protected by the provider company and the seller of the residence.